Repairs Of Expansive Land For Sub Grade Roads - Pratikso Pratikso; Rachmat Mudiyono; Faizal Mahmud (International Conference on Coastal and Delta Areas, 2017)
Subgrade is the most important part in laying the building structure, especially for road construction. The improvement of the quality of road facilities is carried out with initial planning on good pavement layers and should consider the type and strength of subgrade. Road conditions are often damaged in the structure of the road surface layer because it is caused because the structure of the soil in the area often experience shrinkage causing the road becomes cracked and even waving. It is therefore necessary to experiment to stabilize the soil by improving the gradation of mixing the original soil with a larger graded material of rice husk ash, in several experiments with several samples and aggregate mixture to find out the free press value on soil tested both before and after stabilized. The test results showed free press value of comparison between mixing using inorganic salts and lime has increased soil bearing capacity. From the results of this study can be concluded that the addition of the right stabilizer material on expansive soil is good enough to be used to improve the physical and mechanical properties of expansive soil. Keywords: Subgrade, expansive soil, soil stabilization, stabilizer material, soil bearing capacity